Pendampingan Penguatan Minat dan Ketrampilan Masyarakat Desa Wisata dalam Era Industry 4.0 dan Society 5.0 - Diwyarthi, Ni Desak Made Santi; Wiartha, Nyoman Gede Mas; Sadjuni, Ni Luh Gde Sri; Sulistyawati, Ni Luh Ketut Sri; Sabudi, I Nyoman Sukana; Pramana, I Dewa Putu Hendri; Pratama, I Wayan Adi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The Community Service Activity by the Hospitality Management Program, Bali Tourism Polytechnic, took place on Saturday, May 27, 2023. This activity was conducted through training and hands-on practice for 25 MSME (Micro, Small, and Medium-sized Enterprises) owners in Cemagi Tourism Village. The Community Service Activity with the topic of Strengthening the Interests and Skills of Cemagi Tourism Village Residents has had a positive impact in preparing the community to participate in the era of Industry 4.0 and Society 5.0. The development of tourism and the skills of the local community are crucial for improving the well-being and economic potential in Cemagi Tourism Village. The selection of the topic to strengthen interests and skills as baristas was a wise choice, considering the growth of restaurants and accommodations in Badung Regency that require skilled workers in the coffee shop industry